Concurrent aerobic plus resistance exercise versus aerobic exercise alone to improve health outcomes in paediatric obesity: a systematic review and meta-analysis. Issue 3 (16th December 2016) - García-Hermoso, Antonio; Ramírez-Vélez, Robinson; Ramírez-Campillo, Rodrigo; Peterson, Mark D; Martínez-Vizcaíno, Vicente
Abstract : Objective: To determine if the combination of aerobic and resistance exercise is superior to aerobic exercise alone for the health of obese children and adolescents. Design: Systematic review with meta-analysis. Data sources: Computerised search of 3 databases (MEDLINE, EMBASE, and Cochrane Controlled Trials Registry). Eligibility criteria for selecting studies: Studies that compared the effect of supervised concurrent exercise versus aerobic exercise interventions, with anthropometric and metabolic outcomes in paediatric obesity (6–18 years old). The mean differences (MD) of the parameters from preintervention to postintervention between groups were pooled using a random-effects model. Results: 12 trials with 555 youths were included in the meta-analysis. Compared with aerobic exercise alone, concurrent exercise resulted in greater reductions in body mass (MD=−2.28 kg), fat mass (MD=−3.49%; and MD=−4.34 kg) and low-density lipoprotein cholesterol (MD=−10.20 mg/dL); as well as greater increases in lean body mass (MD=2.20 kg) and adiponectin level (MD=2.59 μg/mL). Differences were larger for longer term programmes (>24 weeks). Summary: Concurrent aerobic plus resistance exercise improves body composition, metabolic profiles, and inflammatory state in the obese paediatric population. Trial registration number: CRD42016039807.